Has the Presence of First‐Grade Core Reading Program Academic Vocabulary Changed Across Six Decades?. Issue 4 (19th October 2020) - Fitzgerald, Jill; Relyea, Jackie Eunjung; Elmore, Jeff; Hiebert, Elfrieda H.
Abstract: The purpose of the present study was to examine possible shifts in the presence of academic vocabulary across the past six decades for a continually best‐selling first‐grade core reading program. The authors examined seven program years dating from 1962 to 2013 and computationally determined four categories of academic vocabulary (science, mathematics, social studies, and general academic) in each program. The primary research question was, Did the volume of academic words in a program year rise with advancing years? A secondary supplementary question was, Did the propensity toward academic affinity of a program considered as a whole rise with advancing years? The authors employed two types of academic word measures: (1) A word was deemed to be academic or not, and if it was academic, it was assigned to one of the four academic categories, and then academic words were counted; and (2) a novel measure, academic affinity, was a continuous measure of the probability that a word was academic (in each of the four academic vocabulary categories). The authors conducted Poisson regression modeling and hierarchical generalized linear modeling. The main conclusions were that later first‐grade core reading program years included a moderately higher volume of science, social studies, and total academic words as compared with earlier years and that the science, social studies, and general academic affinity of the program as a whole was statistically higher in later years, but in practical terms, the change was not remarkable.